2012
DOI: 10.5603/cj.2012.0087
|View full text |Cite
|
Sign up to set email alerts
|

Acute and mid-term outcomes of transvenous implant of a new left ventricular quadripolar lead versus bipolar leads for cardiac resynchronization therapy: Results from a single-center prospective database

Abstract: Background: The purpose of this study was to evaluate the feasibility of the use of a quadripolar left ventricular (LV) lead for cardiac resynchronization therapy and to compare its acute and mid-term outcomes with those obtained with bipolar leads. Cardiac resynchronization exhibits a high incidence of problems involving the LV lead when conventional leads are used, and these problems may be minimized by using multipolar leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Additional selective pacing configurations is an obvious advantage of quadripolar leads over bipolar leads. Studies have shown that quadripolar leads are associated with fewer complications, better LV capture threshold, greater improvement in LV ejection fraction (LVEF), and lower mortality rate . In this study, we sought to determine the advantages of quadripolar leads over bipolar leads in CRT outcomes at our center.…”
Section: Introductionmentioning
confidence: 99%
“…Additional selective pacing configurations is an obvious advantage of quadripolar leads over bipolar leads. Studies have shown that quadripolar leads are associated with fewer complications, better LV capture threshold, greater improvement in LV ejection fraction (LVEF), and lower mortality rate . In this study, we sought to determine the advantages of quadripolar leads over bipolar leads in CRT outcomes at our center.…”
Section: Introductionmentioning
confidence: 99%
“…7, 8 Recently, quadripolar LV leads have been designed in order to provide more options for LV pacing. [9][10][11][12][13][14][15] This new lead integrates 4 pacing electrodes that allow a higher number of pacing configurations in device programming as compared with traditional bipolar LV leads. Recent studies suggest that CRT with quadripolar LV lead is associated with a higher implantation success rate and low rates of dislocation and phrenic nerve stimulation (PNS).…”
Section: Study Populationmentioning
confidence: 99%
“…121,122 Quadripolar leads facilitate LV lead implantation by providing more stability, while avoiding apical pacing sites given the distance between electrodes. The introduction of quadripolar leads represents one such recent advance.…”
Section: Sensing In Cardiac Resynchronization Devicesmentioning
confidence: 99%